Surgical Management of External Cervical Resorption Using Different Materials in Relation to the Bone Crest: A Case Report - Andrade Maia, Caroline; Fassarela Marquiore, Larissa; Canal Vasconcellos, Betânia; Farias Teixeira Arruda, Thais Caroline; Benetti, Francine; Rodrigues Amaral, Rodrigo; Tavares, Warley Luciano Fonseca (Iranian Endodontic Journal, 2024)
External cervical resorption is a condition that leads to the loss of hard dental tissues, including enamel, cementum, and dentin. Although it is an aggressive condition, its causes are not yet fully understood. The treatment of resorptions depends on their extent, location and the material used. When managing these lesions, the position of the bone crest and the ability of the periodontal tissue to adhere to the material after setting must be considered. This case report aims to demonstrate a clinical case of external cervical resorption which was treated by a proposed protocol that uses different dentin substitute restorative materials depending on the location of the resorptive area in relation to the bone crest. The success of this treatment depended on the correct use of materials and adequate tissue management. The combination of different materials has shown promising results in treating resorptions in both supra- and infra-osseous areas.